Pengembangan kurikulum merdeka pada pembelajaran maharah qira'ah di MTs Al Maarif 01 Singosari - Nikmah, Lutfiatun (Maliki Interdisciplinary Journal, 2024)
Innovation is a process that must be implemented in various fields of life, including educational activities. The form of innovation applied in education includes aspects of the curriculum, namely the replacement of the Education Unit Curriculum (KTSP) with the 2013 Curriculum (K13) and changing it to the Independent Curriculum. The purpose of these changes is to improve the quality of education in Indonesia. The fact that research in the field of qira'ah learning by educational experts shows that qira'ah learning is not yet effective and efficient and runs very slowly. The research method used in this research is qualitative. This research was carried out at MTs Al-Ma'arif 01 Singosari, this research was conducted from March - May 2023. The subjects of this research were Arabic teachers especially Maharah Qiro'ah teachers. The sample in this study were students in class 7H and 7G of MTs Al-Ma'arif 01 Singosari. Data collection was obtained through PTK. To find out the development of the independent curriculum in maharah qiro'ah learning, First, the teacher makes a lesson plan which is called a teaching module. Second, the implementation of learning in the independent curriculum includes 3 learning implementation activities, namely introduction, core learning, and closing. The third is the assessment stage. In conclusion, as Arabic teachers, we must take the initiative in implementing Arabic learning to arouse students' enthusiasm for learning Arabic.